SOCIAL INTEGRATION ISSUES OF YOUNG PEOPLE LEAVING THE RESIDENTIAL CARE SYSTEM - MATAS, Viorica (Journal of Social Sciences)
Annually, hundreds of young people leave the residential care system, and many of them struggle to integrate socially, often becoming part of deviant or marginalized groups. The aim of the study was to identify the difficulties faced by young people when leaving residential care, in order to determine the social services needed to overcome these challenges. The research methods used were sociological surveys based on questionnaires and focus-group discussions with young people who had left the care system. The difficulties mentioned by young people when leaving the residential care system included: lack of housing, limited financial resources, difficulties in continuing their studies, challenges in finding a job, difficulties accessing medical services, lack of residence permits, and lack of emotional support. Facilitating the social integration process for young people from the care system requires intervention on multiple fronts, including: adapting activities in residential institutions with a greater focus on preparing young people for leaving the system; designating support persons for young people, who would facilitate the social integration process; strengthening cooperation between residential institutions and medical, educational, and employment institutions to ease the transition to independent life for young people; and amending the regulatory framework by diversifying social services that would offer support and foster the successful integration of young people.